Analisis Kinerja Keuangan Menggunakan Metode EVA dan MVA Terhadap Return Saham Yang Dimoderasi Oleh Ukuran Perusahaan - Permatasari, Yiswi Oktavia; Gunarto, Muji (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
Research aim: This study was structured to analyze the effect of financial performance using the EVA and MVA methods on stock returns by including company size as a moderating variable. Design/Methode/Approach: The study uses a quantitative approach. The population of this study is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2022 period, using a purposive sampling technique to obtain a total sample of 27 companies and analyzed with the SEM-PLS approach to test the hypothesis. Research Finding: The results of the study found that company performance significantly affects stock returns using the EVA and MVA methods. However, firm size does not affect stock returns, so the variable firm size cannot moderate financial performance using the EVA and MVA methods on stock returns. This proves that the company has not been able to create added value, and company size cannot determine the continuity of a company's business. Theoretical contribution/Originality: Research is expected to expand knowledge in the field of finance and can be used as a reference in conducting further research. Practitioner/Policy implication: The study's results are expected to be a consideration and input in improving performance, especially in making policies oriented to increasing corporate value in the future. Research limitation: The research is only limited to Economic Value Added (EVA) and Market Value Added (MVA) variables; there are still many interesting value-added variables that can motivate future researchers to use other variables such as the Cash Value Added method, Refined Economic Value Added, Financial Value Added and so on.